The interdependence of the main indicators of five methods applied to determine the lactate anaerobic threshold judo athletes - Sterkowicz, S.; Gabrys, T.; Szmatlan-Gabrys, U.; Stanula, A.; Garnys, M. (Archives of Budo, 2016)
Background and Study Aim: In the practice of sport training the anaerobic threshold (LT2) is sought using a whole range of methods. As a result, different LT2 values are obtained and applied to programme endurance training. The aim of the research are the relationships between the main indicators of the five methods applied to determine the lactate anaerobic threshold judo athletes.